Dietary Anthocyanins Mitigate High-Fat Diet-Induced Hippocampal Inflammation in Mice - Muhammad, Imani (2024)
Background: Obesity and consumption of high-fat diets (HFD) are associated with intestinal permeabilization and increased paracellulartransport of endotoxins, which can promote neuroinflammation. Inflammation can affect the hypothalamic pituitary adrenal (HPA) axis,which controls responses to stress and downregulates the brain-derived neurotrophic factor (BDNF), which can promote anxiety anddepression, conditions frequently found in obesity. We previously showed that consumption of anthocyanins (AC) mitigate HFD-inducedinsulin resistance, intestinal permeability, and inflammation.Objectives: This study investigated if a dietary supplementation with a cyanidin- and delphinidin-rich extract (CDRE) could counteractHFD/obesity-induced hippocampal inflammation in mice.Methods: C57BL/6J male mice were fed for 14 wk on one of the following diets: 1) a control diet containing 10% total calories from fat (C),2) a control diet supplemented with 40 mg AC/kg body weight (BW) (CAC), 3) a HFD containing 60% total calories from fat (lard) (HF), or4) the HFD supplemented with 2, 20, or 40 mg AC/kg BW (HFA2, HFA20, and HFA40, respectively). In plasma and in the hippocampus,parameters of neuroinflammation and the underlying cause (endotoxemia) and consequences (alterations to the HPA and BDNF downregulation)were measured.Results: Consumption of the HFD caused endotoxemia. Accordingly, hippocampal Tlr4 mRNA levels were 110% higher in the HF group,which were both prevented by CDRE supplementation. Consumption of the HFD also caused: 1) microgliosis and increased expression ofgenes involved in neuroinflammation, that is, Iba-1, Nox4, Tnfα, and Il-1β, 2) alterations of HPA axis regulation, that is, with low expressionof mineralocorticoid (MR) and glucocorticoid (GR) receptors; and 3) decreased Bdnf expression. Supplementation of HFD-fed mice withCDRE mitigated neuroinflammation, microgliosis, and MR and BDNF decreases.Conclusions: CDRE supplementation mitigates the negative effects associated with HFD consumption and obesity in mouse hippocampus,in part by decreasing inflammation, improving glucocorticoid metabolism, and upregulating BDNF.